Using gamification to increase students’ motivation: our experience in teaching research methodology class - Jaffri, Hadijah (2017)
As academicians, teaching is one of the core businesses other than research and publication. Improving one’s teaching practice entails a continuous and conscious effort on conducting research in teaching.This is in line with the spirit of Scholarship of Teaching and Learning (SOTL) which emphasizes on the active, conscious and continuous act of research in teaching by academic staff with specific aims to share it with other fellow academic staff later on through scholarly writing or publication.This paper is about our experience using gamification in our research methodology class which is perceived as a theories-laden class.Research methodology involves a systematic outline of decisions in exploring an issue of a research which entails a researcher to be aware of researchable issues and the processes involve to investigate those issues.Teaching research methodology course demands and challenges us as instructors to enable the students to understand various concepts related to research methodology and also to apply what they understand into research actions ethically. However, our post graduate students who are majority work as teachers find it difficult to stay motivated to read research methodology textbooks and stay focused in class during lectures and discussions. To engage students to become more alert and motivated in class, we use gamification to enhance students’ engagement and motivation until the end of class escpecially when there are discussions based on their reading of specific topics.The use of Kahoot! and Quizziz at the end of classes not only helps the students to focus on the discussion but also it serves as formative assessment for the students to assess the progress of their own learning. The features in online quizzes such as Kahoot! and Quizziz, for example, are easy to use and unlike pencil-and-paper test, it has game mechanics that are appealing to the students.To assess students’ perception about gamification, we asked them to provide feedbacks on our classroom activities using one-minute paper notes. It was found that students enjoy the activities using gamification and the activities also sparks their interest to improve on their teaching practice as teachers.